A life-threatening case of drug-induced agranulocytosis - Dutta, N. N.; Datta, Dhruba Jyoti; Koduru, Praneeth Kumar; Rajpurohit, Megha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
A 26 year old hyperthyroidic female with prescribed carbimazole intake from 1 month presented with intermittent low grade fever, sore throat and dysphagia since last 15 days. She appeared very weak and pale. On clinical evaluation, TLC was found very low and DLC showed decreased neutrophil percent. Carbimazole was suspected as the cause and immediately stopped. G-CSF (Filgrastim) was started along with other conservative management and TLC started to rise gradually. On 12th day from admission, she developed acute pain abdomen and diagnosed as having intestinal perforation for which she was immediately operated but unfortunately expired 6 hours after surgery. Drug-induced agranulocytosis can be so fatal that if not diagnosed and treated early, can lead to death due to its widespread rapid systemic derangement.